Heart rate variability profiling tests to forecast competitive progress of 15-16 years old elite ice hockey players - Surina-Marysheva, E. F.; Erlikh, V. V.; Korableva, Yu. B.; Kantyukov, S. A. (Theory and Practice of Physical Culture, 2019)
The study was designed to rate benefits of the heart rate variability profiling tests to forecast competitive progress of 15-16 year old elite ice hockey players, with VNS-MICRO Test System (made by NeuroSoft, Russia) applied for the study purposes. The heart rate variability profiles were obtained using the standard HRV timing method, spectral analysis and pulsometry; plus the vegetative reactivity in parasympathetic department (30:15) and the vegetative reactivity typing methods. The individual competitive progress was rated for 4 years since graduation from the Olympic Reserve Sport School. The test data were processed using Statistica 10.0 software toolkit with its R-language. The individual sport career forecasts and scenarios were generated using Random Forest modeling tools with the relevant set of the most informative progress criteria. The study showed benefits of the heart rate variability profiling tests for the competitive progress forecasts in youth elite ice hockey; and gives analyses of the heart rate variability variation profiles of the leading junior players in the competitive periods.